2015
DOI: 10.1016/j.neuron.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Modular Representation of Luminance Polarity in the Superficial Layers of Primary Visual Cortex

Abstract: Summary The spatial arrangement of luminance increments (ON) and decrements (OFF) falling on the retina provides a wealth of information used by central visual pathways to construct coherent representations of visual scenes. But how the polarity of luminance change is represented in the activity of cortical circuits remains unclear. Using wide-field epifluorescence and two-photon imaging we demonstrate a robust modular representation of luminance polarity (ON or OFF) in the superficial layers of ferret primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 71 publications
5
54
1
Order By: Relevance
“…Across all measured neuronal subtypes, we found that similarity in orientation preference between nearby cells was significantly greater than predicted by a random shuffle (Figure 2I, p<.001 by bootstrap test for GAD+ (n = 3 volumes), SOM+ (n = 3 volumes), PV+ (n = 3 volumes), and EXC (n = 3 volumes), n = 1000 shuffles), and that this spatial clustering of cells by orientation preference decayed over distances consistent with the wavelength of the orientation preference map in the ferret (Muller et al, 2000; Smith et al, 2015b). Likewise, the spatial organization of direction preference among GABAergic neurons (Supplementary Figure 2E), was significantly greater than predicted by a shuffle (p < .001 by bootstrap test for shuffle vs. GAD+ (n = 3 volumes), SOM+ (n = 3 volumes), PV+ (n = 3 volumes), and EXC (n = 3 volumes), n = 1000 shuffles).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Across all measured neuronal subtypes, we found that similarity in orientation preference between nearby cells was significantly greater than predicted by a random shuffle (Figure 2I, p<.001 by bootstrap test for GAD+ (n = 3 volumes), SOM+ (n = 3 volumes), PV+ (n = 3 volumes), and EXC (n = 3 volumes), n = 1000 shuffles), and that this spatial clustering of cells by orientation preference decayed over distances consistent with the wavelength of the orientation preference map in the ferret (Muller et al, 2000; Smith et al, 2015b). Likewise, the spatial organization of direction preference among GABAergic neurons (Supplementary Figure 2E), was significantly greater than predicted by a shuffle (p < .001 by bootstrap test for shuffle vs. GAD+ (n = 3 volumes), SOM+ (n = 3 volumes), PV+ (n = 3 volumes), and EXC (n = 3 volumes), n = 1000 shuffles).…”
Section: Resultssupporting
confidence: 53%
“…GABAergic neurons in the visual cortex of carnivores exhibit selective responses for stimulus features such as orientation and direction of motion (Azouz et al, 1997; Cardin et al, 2007; Hirsch et al, 2003; Keller and Martin, 2015; Martin et al, 1983), suggesting a potentially different organizing principle for interneuron wiring. However, this interpretation is complicated by the spatial clustering of neurons with similar functional properties into columnar maps in the carnivore and primate (Blasdel and Salama, 1986; Grinvald et al, 1986; Kara and Boyd, 2009; Nauhaus et al, 2012; Ohki et al, 2006; Smith et al, 2015b), which is not present in the rodent (Ohki et al, 2005; but see Ringach et al, 2016). As a result, the selective responses of GABAergic neurons in species with columnar maps could arise from the same non-specific local pooling principle applied to an environment in which nearby pyramidal neurons have similar functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the resulting OFF-anchored columnar architecture enables emergence of an additional orderly representation of absolute spatial phase—a property that contains a wealth of information about the visual scene that can be used to efficiently encode spatial patterns 23,24 , motion 25 , and depth 26 . We emphasize that the modular representation of absolute spatial phase preference demonstrated here is distinct from the modular representation of polarity preference that has been described in cat 34 and ferret layer 4, and more recently in ferret layer 2/3 27 . Despite species differences in the representation of polarity, electrophysiological studies in layer 4 of the cat visual cortex suggest that there are common rules governing the convergence of ON and OFF inputs to build orientation selective simple cells, and that the modular representation of absolute spatial phase is a general principle of cortical organization common to a broad range of species with well-developed columnar architecture 28 .…”
contrasting
confidence: 66%
“…The combined input from subcortical ON- and OFF-center pathways has long been recognized as the likely substrate for V1 orientation selectivity (Hubel and Wiesel, 1962). Studies in the carnivore have shown columnar biases of ON-OFF polarity in geniculate afferents (Jin et al, 2008; McConnell and LeVay, 1984; Norton et al, 1985; Smith et al, 2015; Zahs and Stryker, 1988) and V1 (Smith et al, 2015; Wang et al, 2015), which could be a scaffold for orientation maps (Jin et al, 2011; Kremkow et al, 2016; Lee et al, 2016; Miller, 1994; Paik and Ringach, 2011). It seems possible that OD and ON/OFF columnar biases are systematically aligned to produce the orthogonality between OD and orientation maps in the cat (Crair et al, 1997).…”
Section: Discussionmentioning
confidence: 99%